2011
DOI: 10.1042/bst0391102
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress and antioxidant enzymes in Crohn's disease

Abstract: There is increasing interest in oxidative stress being a potential aetiological factor and/or a triggering factor in Crohn's disease, rather than a concomitant occurrence during the pathogenesis of the disease. Recent research has shown that the immune mononuclear cells of Crohn's disease patients are induced to produce hydrogen peroxide (H2O2). Similarly, the regulation of antioxidant enzymes during disease in these cells has been unravelled, showing that SOD (superoxide dismutase) activity and GPx (glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 36 publications
2
73
1
1
Order By: Relevance
“…Altered mesenteric circulation, intestinal microcirculation, and intestinal ischemia are potential etiologic factors in IBD, although their involvement could be secondary (127). The association of ROS with IBD is evident from the observation that increased ROS and decreased antioxidant levels contribute toward major pathogenic mechanisms in IBD (58,126 (186) and "in IBD, the fuse appears to be lit" (42).…”
Section: Ibds (Ulcerative Colitis Crohn's Disease)mentioning
confidence: 97%
See 1 more Smart Citation
“…Altered mesenteric circulation, intestinal microcirculation, and intestinal ischemia are potential etiologic factors in IBD, although their involvement could be secondary (127). The association of ROS with IBD is evident from the observation that increased ROS and decreased antioxidant levels contribute toward major pathogenic mechanisms in IBD (58,126 (186) and "in IBD, the fuse appears to be lit" (42).…”
Section: Ibds (Ulcerative Colitis Crohn's Disease)mentioning
confidence: 97%
“…Catalase-expressing pathogens such as Campylobacter jejuni (10), H. pylori (198), Helicobacter hepaticus (95), and enterobacteriaceae family bacteria (281) (196). Crohn's disease patients show permanent suppression of catalase activity in their mononuclear cells (126). Genetically modified Lactobacilli capable of producing catalase have been shown to reduce tumor in colon (75) and colitis in mice (166).…”
Section: Catalasementioning
confidence: 99%
“…Because activation of the Nrf2 pathway is cytoprotective in the colon (Khor et al, 2006;Theiss et al, 2009) and CDDO-Im induces transcription of Nrf2-target genes such as NQO1 and GCLC in the stomach, small intestine, and colon (Yates et al, 2007), the SOs should also be effective against conditions such as Crohn's disease, inflammatory bowel disease, and ulcerative colitis. In these diseases, oxidative stress and inflammation can drive pathogenesis (Iborra et al, 2011;Strober and Fuss, 2011).…”
Section: E Liver Diseases and Other Diseases Of The Digestive Systemmentioning
confidence: 99%
“…Recent evidence suggests that oxidative stress caused by reactive oxygen species (ROS) is an important factor involved in the onset and development of intestinal inflammation. Furthermore, it has also been demonstrated that disruptions in the antioxidant defense system are involved in the pathophysiology of IBDs (4,5). Therefore, it is important to investigate the oxidative stress-related pathogenesis of IBDs.…”
Section: Introductionmentioning
confidence: 99%